Climate, vegetation and fire history during the past 18,000 years, recorded in high altitude lacustrine sediments on the Sanetti Plateau, Bale Mountains (Ethiopia) - Mekonnen, Betelhem; Glaser, Bruno; Zech, Roland; Zech, Michael; Schlütz, Frank; Bussert, Robert; Gil-Romera, Graciela; Nemomissa, Sileshi; Bekele, Tamrat; Bittner, Lucas; Solomon, Dawit; Manhart, Andreas (Springer, 2022)
Low-altitude lakes in eastern Africa have long been investigated and have provided valuable information about the Late Quaternary paleohydrological evolution, such as the African Humid Period. However, records often suffer from poor age control, resolution, and/or ambiguous proxy interpretation, and only little focus has been put on high-altitude regions despite their sensitivity to global, regional, and local climate change phenomena. Here we report on Last Glacial environmental fluctuations at about 4000 m asl on the Sanetti Plateau in the Bale Mountains (SE Ethiopia), based on biogeochemical and palynological analyses of laminated lacustrine sediments. After deglaciation at about 18 cal kyr BP, a steppe-like herb-rich grassland with maximum Chenopodiaceae/Amaranthaceae and Plantago existed. Between 16.6 and 15.7 cal kyr BP, conditions were dry with a desiccation layer at ~ 16.3 cal kyr BP, documenting a temporary phase of maximum aridity on the plateau. While that local event lasted for only a few decades, concentrations of various elements (e.g. Zr, HF, Nb, Nd, and Na) started to increase and reached a maximum at ~ 15.8–15.7 cal kyr BP. We interpret those elements to reflect allochthonous, aeolian dust input via dry northerly winds and increasingly arid conditions in the lowlands. We suggest an abrupt versus delayed response at high and low altitudes, respectively, in response to Northern Hemispheric cooling events (the Heinrich Event 1). The delayed response at low altitudes might be caused by slow negative vegetation and monsoon feedbacks that make the ecosystem somewhat resilient. At ~ 15.7 cal kyr BP, our record shows an abrupt onset of the African Humid Period, almost 1000 years before the onset of the Bølling–Allerød warming in the North-Atlantic region, and about 300 years earlier than in the Lake Tana region. Erica pollen increased significantly between 14.4 and 13.6 cal kyr BP in agreement with periodically wet and regionally warm conditions. Similarly, intense fire events, documented by increased black carbon, correlate with wet and warm environmental conditions that promote the growth of Erica shrubs. This allows to conclude that biomass and thus fuel availability is one important factor controlling fire events in the Bale Mountains.